2021
DOI: 10.3389/fcell.2021.693154
|View full text |Cite
|
Sign up to set email alerts
|

Linking Chromosomal Silencing With Xist Expression From Autosomal Integrated Transgenes

Abstract: Xist is the master regulator of X-Chromosome Inactivation (XCI), the mammalian dosage compensation mechanism that silences one of the two X chromosomes in a female cell. XCI is established during early embryonic development. Xist transgene (Tg) integrated into an autosome can induce transcriptional silencing of flanking genes; however, the effect and mechanism of Xist RNA on autosomal sequence silencing remain elusive. In this study, we investigate an autosomal integration of Xist Tg that is compatible with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…POU3F4 was the only suggested variant in the current analysis that is a transcription factor. In our published sex-specific network analysis of gene expression data in normal lung tissue, POU3F4 demonstrated sexed biased targeting of 15 X chromosome genes, 14 of which escape XCI, including two important XCI regulators, XIST and JPX (Additional file 1 : Figure S5) [ 53 , 54 ]. This points to sex-biased genetic variants as one mechanism implicated in sex-biased transcriptional targeting.…”
Section: Discussionmentioning
confidence: 99%
“…POU3F4 was the only suggested variant in the current analysis that is a transcription factor. In our published sex-specific network analysis of gene expression data in normal lung tissue, POU3F4 demonstrated sexed biased targeting of 15 X chromosome genes, 14 of which escape XCI, including two important XCI regulators, XIST and JPX (Additional file 1 : Figure S5) [ 53 , 54 ]. This points to sex-biased genetic variants as one mechanism implicated in sex-biased transcriptional targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Through a combination of these approaches, Su et al demonstrated that dose-sensitive overexpression of RAD21 caused by trisomy 8 helped mitigate the replication stress induced by the oncogenic EWS-FLI1 fusion in Ewing sarcoma (Su et al 2021 ). Next to this, integration of XIST, the long non-coding RNA (lncRNA) that inactivates one of the X chromosomes in females (Boumil and Lee 2001 ; Engreitz et al 2013 ; Simon et al 2013 ), was found to fully inactivate a copy of chr21 (Jiang et al 2013 ; Chiang et al 2018 ; Czermiński and Lawrence 2020 ), and to silence parts of mouse chr1 and human chromosomes 1p, 3q, 4q, 7p, 7q, 8p, 12q, and 15q (Kelsey et al 2015 ; Loda et al 2017 ; Naciri et al 2021 ). Although less specific than RNAi or CRISPRi, the epigenetic silencing potential of this lncRNA could be leveraged to pinpoint which part of the chromosome of interest is responsible for certain aneuploidy-related phenotypes.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…First instances of lncRNA directly engaged in the production of repressive chromatin are found in Xist [96]. Furthermore, Xist through particular RNA sequences, organizes the anchoring of chromatin modifiers to one of the two X chromosomes, enabling transcriptional silencing [97].…”
Section: Lncrnasmentioning
confidence: 99%